Analisys of Book i of the New Code of Civil Procedure: A Reflex of the Phenomenon of Constitucionalization of Civil Procedure - Costa, Yvete Flavio da (2016)
This article aims to analyze the Book I of the New Code of Civil Procedure, called "The civil procedural rules" linking it to the constitutionalization process that civil process has going by after the enactment of the 1988 Federal Constitution. This is because, since its enactment, the Democratic Constitution became maximum vector of the entire legal system, so that all laws must  comply  with  its  principles  and  rules,  under  penalty  of  being  considered unconstitutional. The previous Code, enacted in 1973, before the current Constitution, had no such concern because at that time, the maximum vector law was the Civil Code of 1916. So in that text, there was not some of the fundamental assumptions for valid and regular development of civil procedure, such as contradictory. With that in mind, the legislator brought in this chapter, a kind of law of introduction to civil procedure rules, regulating the application of the process in time and space, and also brings the constitutional principles that were not explicitly present in the encoded text before.. The present article is justified by the need to carry out a deeper study of the constitution of civil procedure, with a view to the subject nowadays. In order to enable the thematic deepening of the subject, it was employed the logical deductive and inductive methods logical, since the research was based on deductive research of new legislation.